Mercies in the American Desert : Poems - Landry, Benjamin (Book collections on Project MUSE., 2021)
"Reflecting on the Salem witch trials, Puritan minister Cotton Mather cautioned his audience against the moral temptations of the unknown wild, located in what he termed an American desert. Today, we understand that our troubles have their origins not in some ambiguous beyond; rather, they are of our own making. Benjamin Landry's "Mercies in the American Desert" attempts a clear-eyed reckoning with the people and the nation we have become, from gun violence to state-sanctioned racism and brutality. This vivid collection considers a range of bodies encompassing the geographic, the personal, and the political. It locates solace in movement, sound, and observation, as when Pina Bausch heron-dances down a traffic median, or when the expansive form of a surfacing manta ray teaches us how to breathe again. Incorporating short bursts of prose poem alongside longer meditations, and working in both alliterative and narrative modes, "Mercies in the American Desert" conjures a redemptive wildness for our time"--